Midwifery education in Ireland – The quest for modernity. (February 2016) - O'Connell, Rhona; Bradshaw, Carmel
Abstract: Midwifery education in Ireland has undergone significant changes in recent years including the introduction of direct entry midwifery programmes and a transfer of education to the university sector. While this has provided increased educational opportunities for midwives, the challenge for midwife educators is to prepare students for the increasing complexities of maternity care with a focus on obstetric risk and maternal morbidities with the need to educate midwifery students to support normality and provide woman centred care. The Nursing and Midwifery Board of Ireland has recently produced new Standards and Requirements for midwifery education and Practice Standards for midwives. This article provides information on midwifery education in Ireland and the documents that support the development of the profession.